Minuartia alpuensis (Caryophyllaceae), a new endemic species from inner Anatolia, Turkey - Çi̇lden Emre; Gençay Çelemli̇ Ömür (Phytotaxa, 2020)
In this study a new species from Turkey, Minuartia alpuensis (Caryophyllaceae), is described and illustrated, and its taxonomic relationships are discussed. The distribution of the new species, its ecology and conservation status are given, and an identification key is provided. Pollen structures of both new and related taxa are examined.